(untitled) (Global Journal of Sciences, 2025)
In this article, we presented the goodness-of-fit tests for the inverse Ishita distribution with one parameter based on complete sample. Moreover, the maximum likelihood estimation method was used to estimate the unknown parameter of the distribution. In addition, a Monte Carlo simulation was also performed to verify the behavior of the maximum likelihood estimator. Ultimately, we applied the proposed distribution on renewable energy data in Saudi Arabia and compared it with Weibull and Shanker distributions.